2008
DOI: 10.1371/journal.pone.0002170
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Restraint Stress Generates Two Distinct Behavioral and Neurochemical Profiles in Male and Female Rats

Abstract: Prenatal Restraint Stress (PRS) in rats is a validated model of early stress resulting in permanent behavioral and neurobiological outcomes. Although sexual dimorphism in the effects of PRS has been hypothesized for more than 30 years, few studies in this long period have directly addressed the issue. Our group has uncovered a pronounced gender difference in the effects of PRS (stress delivered to the mothers 3 times per day during the last 10 days of pregnancy) on anxiety, spatial learning, and a series of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
259
6
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(302 citation statements)
references
References 117 publications
(86 reference statements)
26
259
6
11
Order By: Relevance
“…By contrast, prenatal social stress in late pregnancy does not appear to affect anxiety-type behaviour in female offspring (Brunton & Russell 2010), except when given in combination with another psychological stressor (restraint) in early-mid pregnancy (Bosch et al 2007). Other studies using different prenatal stress models in rats have also reported sex differences (Zagron & Weinstock 2006, Mueller & Bale 2008, including reduced anxiety in Effects of social stress during pregnancy R179 prenatally stressed females compared with males (Zuena et al 2008).…”
Section: Effects On Anxiety-like Behaviour In Prenatally Stressed Offmentioning
confidence: 99%
“…By contrast, prenatal social stress in late pregnancy does not appear to affect anxiety-type behaviour in female offspring (Brunton & Russell 2010), except when given in combination with another psychological stressor (restraint) in early-mid pregnancy (Bosch et al 2007). Other studies using different prenatal stress models in rats have also reported sex differences (Zagron & Weinstock 2006, Mueller & Bale 2008, including reduced anxiety in Effects of social stress during pregnancy R179 prenatally stressed females compared with males (Zuena et al 2008).…”
Section: Effects On Anxiety-like Behaviour In Prenatally Stressed Offmentioning
confidence: 99%
“…spatial tasks; Darnaudery and Maccari 2008). Many studies report sexdependent effects, with males typically showing an increase in anxiety after prenatal stress and dysmasculinised behaviours, whereas females show converse behavioural responses (Zuena et al 2008). The release of glucocorticoids by the stressed mother, which can cross the placenta to affect the developing offspring, appears to mediate these responses (Mesquita et al 2009;Harris and Seckl 2011) and changes to over 700 genes in the fetus, in a region-and sex-specific manner, have been reported (Mychasiuk et al 2011).…”
Section: Animal Behaviour and Welfarementioning
confidence: 99%
“…Prenatal stress produces long-lasting deficits in the production and survival of new neurons into adulthood (Koo et al, 2003;Lemaire et al, 2000;Zuena et al, 2008). A recent study indicates that infection during pregnancy reduces cell proliferation and neurogenesis in both juvenile and adult offspring (Lin and Wang, 2014).…”
Section: Effects Of Early-life Experiences On Adult Neurogenesis and mentioning
confidence: 99%